The Dynamic Effects of Personal and Corporate Income Tax Changes in the United States: Comment - Jentsch, Carsten; Lunsford, Kurt G. (American Economic Review, 2019)
Mertens and Ravn (2013) estimate impulse response functions (IRFs) from income tax changes in a structural vector autoregression (SVAR) by using narrative accounts of tax liability changes as proxy variables. To produce confidence intervals for their IRFs, they use a residual-based wild bootstrap, which has subsequently become popular in the proxy SVAR literature. We argue that their wild bootstrap is not valid, producing confidence intervals that are much too small. Using a residual-based moving block bootstrap that is proven to be asymptotically valid, we reestimate confidence intervals for Mertens and Ravn’s (2013) IRFs and find no statistically significant effects of tax changes on output, labor, and investment. (JEL E23, E62, H24, H25, H31, H32)